Antecedents of affective organizational commitment and turnover intention of academics in selected private universities in Malaysia - Lew, Tek Yew (Universiti Malaysia Sarawak (UNIMAS), 2011)
The private universities are playing important roles in offering high quality education to Malaysian and international students, thus contributing towards the aims of making Malaysia an international education hub. This study empirically investigated the influence of three selected HR practices, namely pay level satisfaction, career development opportunities and work-family support, POS and three mediating variables, namely felt obligation, trust in management and professional commitment on two focal variables, namely affective organizational commitment and turnover intention in the context of academics working with private universities in Malaysia. The underlying theory for this study is the Organizational Support Theory. The objectives of the study were achieved using a quantitative survey method. A pilot study with 134 academics from one private university was undertaken to ensure the validity and reliability of the research instrument as well as identifying the best fitting structural model that would explain the data collected.) For the actual study, a total of four private universities gave approval for this study to be conducted and a total of 202 valid responses were received from the academics, yielding a response rate of 20.2%. The structural equation modeling (SEM) technique was used to test the validity of the overall measurement and structural model and the hypothesized relationships between the latent constructs. This study found that the academics' perceived career development opportunities positively influenced -the level of POS and POS had a direct positive relationship with affective organizational commitment. Besides, POS has not only a direct influence on organizational commitment, but also an indirect impact via felt obligation, confirming the partial mediator effect of felt obligation. Another interesting finding of the study was that the influence of POS on turnover intention is only through the indirect effect via affective organizational commitment. The results of this study add to our knowledge about the social exchange mechanisms or process that link HR practices with the employees'affective organizational commitment and turnover intention. This study sheds some important implications on the effective management of employees in general, and academics in particular. Future research directions include employing the longitudinal research design to confirm the direction of causality ofthe constructs of this study; including other HR practices, mediating variables and employee behaviors into the model; and extending the study to other institutions of higher learning.